Managed access technology to combat contraband cell phones in prison: Findings from a process evaluation. (February 2018) - Grommon, Eric
Highlights: A process evaluation identifies operational challenges and lessons learned of managed access. Managed access captures large volumes of contraband cellular transmissions. Managed access requires significant personnel support to be effective. Implementation and effectiveness requires complex partnerships with commercial carriers. Managed access is not a singular solution to contraband cell phones. Abstract: Cell phones in correctional facilities have emerged as one of the most pervasive forms of modern contraband. This issue has been identified as a top priority for many correctional administrators in the United States. Managed access, a technology that utilizes cellular signals to capture transmissions from contraband phones, has received notable attention as a promising tool to combat this problem. However, this technology has received little evaluative attention. The present study offers a foundational process evaluation and draws upon output measures and stakeholder interviews to identify salient operational challenges and subsequent lessons learned about implementing and maintaining a managed access system. Findings suggest that while managed access captures large volumes of contraband cellular transmissions, the technology requires significant implementation planning, personnel support, and complex partnerships with commercial cellular carriers. Lessons learned provide guidance for practitioners to navigate these challenges and for scholars to improve future evaluations of managed access.